LANGUAGE AND CULTURE: THEIR INTERDEPENDENCE AND IMPACT ON COMMUNICATION - Karimberganova Shahnoza Muxammad qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Language  and  culture  form  intricate  relationships  as  they  influence each  other  and  shape  identity  and  communication  among  humans.  This  paper  will analyze  the  interplay  between  culture  and  language  by  highlighting  how  values determine expressions of culture and vice versa. It will also cover  how language is linked to social transmission of norms and values associated with cultures. This paper will  also  highlight  the  role  of  culture  competence  for  effective  intercultural communication and how education is integral to social awareness for culture. It will also cover how loss of languages affects culture because of globalization. It will thus conclude that effective interplay between culture and language is integral for successful communication  and  mutual  social  understanding  among  humans  in  this  modern interrelated social world.